Identification of impact of digital technologies on business management systems and reducing innovation risks in the digital age - Kopbolsyn, Bibigul; Jakupova, Assel; Bazarova, Bakytgul; Talapbayeva, Gulnar; Yerniyazova, Zhanat (Eastern-European Journal of Enterprise Technologies, 2026)
The object of this study is the innovative activity of enterprises and mechanisms for managing innovation risks in the context of the digital transformation of the economy of the Republic of Kazakhstan. The problem to be solved is the cost-effectiveness of integrating digital technologies into innovation risk management systems. This paper examines theoretical approaches to defining innovation activity, broadens its concept, and investigates the impact of digitalization on innovation risk management processes at enterprises. An analysis of the dynamics of the country’s gross domestic expenditure, innovation activity indicators, and the international ICT development index was conducted, revealing trends in Republic of Kazakhstan’s sustainable digital development. The study’s results demonstrate that digitalization is a driving force for innovation and a tool for improving the effectiveness of innovation risk management. To this end, the costs associated with the development of the digital economy were analyzed, revealing that these expenditures in the Republic of Kazakhstan increased by 63.8% between 2019 and 2024. The study also found that the level of innovation activity at enterprises increased from 10.1% to 14.2%. A key finding of the study is that the implementation of digital solutions reduces losses from innovation risks by 18–34%, while the economic benefits for enterprises, depending on their size, range from 2.16 to 267.2 thousand USD. Therefore, the scope of application includes enterprises of various sizes that need to improve their financial performance through the development of various innovation risk management systems and the implementation of digital transformation programs